Informal cross-border trade in Africa: How much? Why? And what impact? - Bouët, Antoine; Pace, Kathryn; Glauber, Joseph W. (International Food Policy Research Institute, 2018)
Informal cross-border trade (ICBT) represents a prominent phenomenon in Africa. Several studies suggest that for certain products and countries, the value of informal trade may meet or even exceed the value of formal trade. This paper provides a review of existing efforts to measure informal trade. We list 18 initiatives aimed at measuring ICBT in Africa. The paper also summarizes discussions conducted with many stakeholders in Africa between December 2016 and May 2018 regarding the measurement, the determinants, and the implications of ICBT. The methodologies used to measure ICBT in Africa differ widely, but they do confirm that informal trade in Africa is both sizeable and volatile. Both evidence on the determinants of ICBT and discussions with stakeholders suggest that policies should aim to reduce the existing costs associated with formal trade and provide positive incentives for traders and producers to move into the formal economy in order to avoid the loss of economic potential stemming from informal trade.